Drop-weight impact tests on free from damage beam to column connections. (May 2022) - D'Antimo, M.; Latour, M.; Demonceau, J.F.
Abstract: Modern standards require the design of resilient structures, highlighting the need for systems able to assure life safety and an easy repairability. Indeed, a resilient design includes the conception and the realization of a structure able to sustain accidental or exceptional events with limited and easy-to-repair damages. Within this framework, steel Moment Resisting Frames (MRFs) equipped with Slide Hinge Joints, have proved to be extremely efficient for the seismic performance and damage avoidance. However, to date, limited knowledge exists on their behaviour under exceptional events and significant research efforts are still required. In order to provide a contribution to fill this gap, this paper focuses on the behaviour of SHJs with Symmetric Friction Dampers (SFDs) under drop-weight impact. SHJs are normally designed to act as the dissipative fuse of MRFs under seismic loadings. However, they can be also effectively exploited to improve the robustness of steel buildings through the increase of the local ductility, which may ensure also the activation of catenary effects in beams and tying forces. The response of MRFs equipped with such a joint under extreme dynamic loading condition is not straightforward. It requires a deep knowledge of their behaviour as a function of the strain rate. In this paper the results of six drop weight impact tests on double-sided SHJs are presented and a 3D finite element model is developed in ABAQUS software. A parametric analysis is then performed to investigate the influence of the key parameters affecting the joint behaviour, namely: the impact velocity, the impact mass and the impact energy. In order to characterize the joint behaviour under impact, the paper provides a correlation between the dissipation rate of the joint, under impact, and the input energy. The work is limited to a geometric range and to the joint typology here considered, however, the methodology and the results can be generalized. Overall, the joints perform better under higher velocities rather than higher masses due to strain rate effects. However, a clear correlation between the DIF and the velocity of rotation of the joint is difficult to establish. Graphical abstract: Unlabelled Image Highlights: Six drop-weight impact tests on SHJs are presented. A FE Model in Abaqus/Explicit is validated and used to perform parametric analyses. The correlation between strain rate and M, V and E is investigated. The DIF of impacts are given and discussed.